A pilot comparison of phospolipidated lutein to conventional lutein for effects on plasma lutein concentrations in adult people. Issue 1 (December 2015) - DiSilvestro, Robert; Thomas, Sara; Harrison, Earl; Epitropoulos, Alice
Abstract Background The percent absorption of lutein from supplements falls well below that from lutein enriched egg yolk, a rich source of phospholipids. Therefore, a supplement of lutein plus phospholipids was tested for effects on serum accumulation. Methods A 10 day supplementation with a solid-lipid particle (SLP™ ) lutein complex or conventional lutein ester was done in apparently healthy people (both supplement types taken with fat containing meals). Plasma lutein was measured pre- and post-supplementation as well as 7 days after supplementation stopped. Changes within each supplement group were analyzed by pairedt -test; group comparisons were done by unpairedt -test. Results The solid-lipid particle complex lutein gave much higher plasma lutein values than conventional lutein ester. The lutein complex showed superior effects based on absolute mean value after 10 days of supplementation, change in value from baseline to 10 days, and value at 7 days after supplement discontinuation. Conclusions A solid lipid lutein complex strongly increased plasma lutein levels compared to a conventional form.